Formulation And Evaluation of Enteric Coated Microspheres of Acetaminophen - M.Ponmadasamy; Navin Kumar B.V; L.V. Vigneshwaran; M. Senthil Kumar (Genius Journals, 2022)
Microspheres are novel drug delivery systems that are used to control the release of dosage form. The present work is to formulate and evaluate the enteric coated microspheres loaded Acetaminophen using inotropic gelation method for the controlled drug delivery of Acetaminophen. Enteric coated microspheres were prepared by using 2% sodium alginate (SA) aqueous solution with three different concentration (10%, 15%, 20% w/v)of cross linking agent (Cacl2). Followed by coating with 2% hydroxypropyl methylcellulose phthalate. Three formulations were formulated and evaluated for micrometric properties like angle of repose, bulk density, tapped density, Hausner’s ratio, Carr’s index, drug content, In-vitro drug release, SEM analysis and release kinetics. Among all three formulation, formulation 3(F3) showed maximum percentage drug release at 8 hrs (82.20%). So the formulation 3 (F3) is selected as optimized formulation. Thus it can be concluded that all the coated microspheres prolonged and extended the drug release. Therefore, these coated microspheres can be used to control and prolong the drug release effectively and reducing the dosing frequency of Acetaminophen
Keywords: Enteric coated microspheres; Sodium alginate; Calcium chloride; Hydroxyl propyl Methylcellulose